Aβ Assemblies Promote Amyloidogenic Processing of APP and Intracellular Accumulation of Aβ42 Through Go/Gβγ Signaling - Antonino, Magdalena; Marmo, Paula; Freites, Carlos Leandro; Quassollo, Gonzalo Emiliano; Sánchez, Maria Florencia; Lorenzo, Alfredo; Bignante, Elena Anahi (Frontiers in Cell and Developmental Biology, 2022)
Alzheimer´s disease (AD) is characterized by deposition of aggregated species of amyloid beta (Aβ) in the brain, which leads to progressive cognitive deficits and dementia. Aβ is generated by the successive cleavage of the amyloid precursor protein (APP), first by β-site APP cleaving enzyme 1 (BACE1) and subsequently by the γ-secretase complex. Conditions that enhance Aβ generation or reduce its clearance predispose to Aβ aggregation and the development of AD. In vitro studies have demonstrated that Aβ assemblies spark a feedforward loop heightening Aβ production. However, the underlying mechanism remains unknown. Here, we show that oligomers and fibrils of Aβ enhance colocalization and physical interaction of APP and BACE1 in recycling endosomes of human neurons derived from induced pluripotent stem cells and other cell types, which leads to exacerbated amyloidogenic processing of APP and intracellular accumulation of Aβ42. In cells overexpressing mutant forms of APP that are unable to bind Aβ or to activate Go protein, we have found that treatment with aggregated Aβ fail to increase colocalization of APP with BACE1 indicating that Aβ-APP/Go signaling is involved in this process. Moreover, inhibition of Gβγ subunit signaling with βARKct or gallein, prevent Aβ-dependent interaction of APP and BACE1 in endosomes, β-processing of APP and intracellular accumulation of Aβ42. Collectively, our findings uncover a signaling mechanism leading to a feedforward loop of amyloidogenesis that might contribute to Aβ pathology in early stages of AD and suggest that gallein could have therapeutic potential.